PENGARUH PENATAAN KAWASAN KHUSUS PEDESTRIAN DI MALIOBORO KE TERAS MALIOBORO TERHADAP PEREKONOMIAN PKL DAN KEPUASAN - Indrakusuma, Galton Dwita; Wiryawan, bangkit Aditya; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2024)
Most of the narratives suggest that the implementation of the Special Pedestrian Area Arrangement policy in Malioboro in February 2022 had a detrimental effect on the economy of street vendors. Meanwhile, Malioboro has become an icon of Yogyakarta, intended for tourists to stroll around, thus creating issues for both street vendors and pedestrians. This study was conducted to assess the impact of this policy on traders and pedestrians comprehensively, including infrastructure and management efforts, and to evaluate the policy's effectiveness. The objective is to produce comprehensive research by examining it from various perspectives. This research employs a descriptive qualitative approach, gathering data through interviews, followed by data triangulation using observation to validate the data. The research subjects include the Dinas Koperasi dan UKM DIY, vendors and pedestrians. The findings of this research are as follows: (1) The aspect of facilities and infrastructure has a positive influence, facilitating and boosting the local merchant economy. (2) The economic aspect for traders suffers a negative impact due to decreased income and visitor numbers, potentially by 25-50% compared to prerelocation figures. (3) Management efforts have led to increased visitor numbers and improved trader quality and organization. Currently, visitor numbers have increased by approximately 4-5% over the past year. (4) In terms of pedestrians, the policy has a positive influence, contributing to pedestrian satisfaction by bringing numerous benefits. (5) The policy's effectiveness has been demonstrated through successful achievement of target accuracy, timeliness, goal attainment, and real change have been succesfully met